A Recurrent Cryptic MED14-HOXA9 Rearrangement in an Adult Patient With Mixed-Phenotype Acute Leukemia, T/myeloid, NOS - Wang, Qian; Zhang, Ling; Zhu, Ming-qing; Zeng, Zhao; Fang, Bao-zhi; Xie, Jun-dan; Pan, Jin-lan; Wu, Chun-xiao; Wu, Ni; Zhang, Ri; Chen, Su-ning; Dai, Hai-ping (Frontiers in Oncology, 2021)
To define the fusion genes in T/myeloid mixed-phenotype acute leukemia (T/M MPAL), we performed transcriptome sequencing of diagnostic bone marrow samples from 20 adult patients. Our analysis identified a second instance of a recurrent MED14-HOXA9 chimeric gene resulting from the in-frame fusion of exon 23 of MED14 and exon 1 of HOXA9, the first in an adult patient. The MED14-HOXA9 fusion gene was detected in both the diagnostic and relapsed blasts with reverse transcription-polymerase chain reaction and Sanger sequencing. The patient received combined conventional chemotherapy but suffered relapse at 11 months and died of disease progression one year after the initial diagnosis. Our data suggest that MED14-HOXA9 is a cryptic recurrent aberration in T/M MPAL, which might indicate an aggressive clinical course and inferior outcome after conventional chemotherapy. Further studies will be carried out to reveal the effects of the MED14-HOXA9 fusion on the differentiation and proliferation of leukemia stem cells, as well as suitable treatment strategies for this emerging entity.